The Influence of Accreditation, Promotion, and Brand Image on Enrollment Interest, Moderated by Cost, at Universities in Serang City - Iman Hickmatullah; Dhany Isnaeni Dharmawan (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of students' perceptions of Accreditation (X1), Promotion (X2), and Brand Image (X3) on their Interest (Y) in registering, with Cost (Z) serving as a moderating variable. Data were collected from 399 respondents. The validity test results indicate that all research instruments are valid. Meanwhile, the reliability test results show that all variables have Cronbach's Alpha values ranging from